PENGARUH LAYANAN KONSELING KELOMPOK TERHADAP PENGEMBANGAN HARGA DIRI BAGI SISWA BERPRESTASI AKADEMIK RENDAH KELAS VIII C SMPN 6 KOTA BENGKULU - Sihaloho, Ruth Paulin Dipapola; Dharmayana, I Wayan; Sinthia, Rita (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2023)
This study aims to describe the effect of group counseling on increasing the self-esteem of class VIII C students of SMP Negeri 6 Bengkulu City who have low academic achievement. One-group experimental pretest-posttest design was used in this study. The population of this study were 22 students of class VIII C, SMP Negeri 6 Bengkulu City. Purposive sampling was used to select a sample and get a sample of 6 students. Questionnaires and Likert scales were used to collect data. The results of the study showed that there was an influence between group counseling services for increasing self-esteem in students with low academic results, besides that it also strengthened the results of this study. this research is accepted.